The Time Variation of Risk and Return in Foreign Exchange Markets: A General Equilibrium Perspective - Bekaert, Geert (Review of Financial Studies, 1996)
This article successively introduces variable velocity, durability, and habit persistence in a standard two-country general equilibrium model and explores their effects on the variability of exchange rate changes, forward premiums, and the foreign exchange risk premium. A new feature of the model is that agents make decisions at a weekly frequency and face conditionally heteroskedastic shocks. Nevertheless, even the most complex model fails to deliver sufficiently variable risk premiums without causing forward premiums and exchange rates to be excessively variable. Unlike previous models, the model can roughly match the persistence of forward premiums.